A magyarországi pecsenyecsirke-ágazat múltja és jelene, versenyképességének elemzése - Vincze-Lendvai, Edina (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
In Hungary in the last 5 years the meat-production and consumption is uncertain. The habits of the consumers have changed, the meat-prices have grown and new animal-diseases have appeared. The changes reached the poultry-sector too. In my work I show the development of the poultry branch, examined the broiler sector - its most important factors, and made a SWOT-analysis about the competitiveness of this department. .